Innovation dynamics and labor force restructuring with asymmetrically developed national innovation systems. Issue 1 (February 2017) - Santos-Arteaga, Francisco J.; Di Caprio, Debora; Tavana, Madjid; O'Connor, Aidan
Highlights: We present an endogenous growth model of technological assimilation and innovation. National innovation systems determine the accumulation of technological knowledge. Emigration and the advantage of backwardness provide insufficient innovation incentives. Structural inequalities may prevail even within an ideal common market environment. Our results are validated empirically and used to suggest policies for the European area. Abstract: The concept of National Innovation System (NIS) has gained a great deal of intellectual and practical attention over the past three decades. We present an endogenous growth model where the NIS of a country determines its accumulation of technological knowledge and the arrival rate of innovations depends on the distance from the technological frontier to the current technological development level (TDL) of the country. We show how, even within an ideal common market environment and despite the compensatory mechanism provided by migration and the advantage of backwardness enjoyed by the laggard countries, differences in TDLs among countries foster the economic stagnation of technological laggards. That is, the structural consequences derived from technological underdevelopment are persistent and not simply due to the depreciation of human capital, but to the absence of innovation incentives that follows. Numerical simulations and an empirical analysis are performed to illustrate the main results and relate them to the current European common market setting and the innovation policies of its members.